2014
DOI: 10.1038/onc.2014.165
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear translocation of IGF-1R via p150Glued and an importin-β/RanBP2-dependent pathway in cancer cells

Abstract: Mounting evidence has shown that the insulin-like growth factor-1 receptor (IGF-1R) has critical roles in cancer cell growth. This has prompted pharmacological companies to develop agents targeting the receptor. Surprisingly, clinical trials using specific IGF-1R antibodies have, however, revealed disappointing results. Further understanding of the role of IGF-1R in cancer cells is therefore necessary for development of efficient therapeutic strategies. Recently, we showed that IGF-1R is sumoylated and translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 226 publications
5
66
1
1
Order By: Relevance
“…Recently, we showed that the IGF‐1R undergoes SUMOylation, which leads to nuclear translocation and gene activation through binding to enhancers or nuclear proteins (Packham et al, 2015; Sehat et al, 2010; Warsito, Lin, Gnirck, Sehat, & Larsson, 2016; Warsito, Sjöström, Andersson, Larsson, & Sehat, 2012). Introduction of site specific mutations corresponding to three evolutionary conserved SUMOylation sites (Lys1025, Lys1100, and Lys1120) in IGF1R decreased nuclear IGF‐1R (nIGF‐1R) and abolished its gene regulatory effects while retaining IGF‐1R kinase‐dependent signaling (Sehat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that the IGF‐1R undergoes SUMOylation, which leads to nuclear translocation and gene activation through binding to enhancers or nuclear proteins (Packham et al, 2015; Sehat et al, 2010; Warsito, Lin, Gnirck, Sehat, & Larsson, 2016; Warsito, Sjöström, Andersson, Larsson, & Sehat, 2012). Introduction of site specific mutations corresponding to three evolutionary conserved SUMOylation sites (Lys1025, Lys1100, and Lys1120) in IGF1R decreased nuclear IGF‐1R (nIGF‐1R) and abolished its gene regulatory effects while retaining IGF‐1R kinase‐dependent signaling (Sehat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that IGF1R is sumoylated and translocated to the nucleus, which permits the receptor to interact with chromatin, and function as a transcriptional regulator (95)(96)(97). Nuclear IGF1R specifically binds to and functions as a transcriptional activator of its own promoter, and interferes with signaling pathways (98).…”
Section: Interacting With Ecmmentioning
confidence: 99%
“…Miyauchi et al (2012) demonstrated a role of RANBP2 in SUMOylation and localization of MDM2, a major regulator of p53 stability, suggesting therefore a possible indirect implication of RANBP2 in p53 functions. Packham et al (2014) showed that RANBP2 is implicated in the pro-tumorigenic activity of the insulin-like growth factor-1 receptor (IGF-1R), an activator of the PI3K/Akt pathway with key roles in tumorigenesis. The biological activity of IGF-1R depends on its nuclear translocation, which in turn depends on SUMOylation.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The biological activity of IGF-1R depends on its nuclear translocation, which in turn depends on SUMOylation. Packham et al (2014) characterized spatially regulated interactions of IGF-1R, first with dynactin, which transports IGF-1R to NPCs, and therein with importin-β and RANBP2. RANBP2 interacts with and stabilizes sumoylated IGF-1R, enabling its nuclear accumulation and hence the activation of tumorigenic pathways that depend on it.…”
Section: Colorectal Cancermentioning
confidence: 99%